Estudo multicaso da viabilidade econômica da água de reúso no segmento comercial, têxtil e químico na região metropolitana de São Paulo - Neves, Silvia Soares das (2014)
Overall, the amount of water available on earth is superior to the human need. Previously, water was characterized as an inexhaustible good with great abundance. Over the years, the studies and the awareness of the water, as a limited and finite resource, built up the recognition of its importance. In the Metropolitan Region of São Paulo (RMSP), according to the Falkenmark indicator, used by the United Nations to measure water stress, this metropolitan area is classified as a place with "absolute water scarcity". The risk of scarcity generated a search for alternatives to adapt human activities to the limits of the water resources available in nature. One way that has been found is to reuse water. This study aims to compare the economic feasibility of using the publicly supplied reuse water against different alternatives available in the RMSP. Three companies in different industrial fields were surveyed. One of the important missing information about this issue is related to the research question of the present study and to answer it, a survey was held based on a theoretical approach driven by the literature and directed to the topics of interest. The qualitative method was chosen, which comprised a desk review of the companies included in the research context. The study revealed that the use of publicly supplied reuse water is economically viable in the commercial sector, which uses potable water in their operations. For the chemical and textile industries, despite having the lowest cost in its operation, together with the Payback NPV and IRR, the reuse proved to be unviable as an investment. It was also observed the lack of a public policy to encourage the reuse, involving a partnership between the public and private sectors to mitigate the water stress in the RMSP. It is expected that the results of this study can be relevant to both the public and private sectors, due to the need of having an enhanced management of water resources to support public policies not as a mandatory rule, but to encourage the water reuse as a feasible alternative to potable water.